Hermes store at Horniman Circle - Ghosh, Ayan (2023)
The facades of the Circle buildings were designed by James Scott, Chief Engineer of the Elphinstone Land & Press Company, established in 1858 to undertake reclamation projects. The foundation stone was laid in 1864 for the Bank of Bombay, which was the first building developed in the Circle. The remaining buildings were completed by 1873.